Pengaruh Administrasi Perpajakan Modern, Pelayanan, dan Sanksi terhadap Kepatuhan Wajib Pajak Orang Pribadi di KPP Pratama Medan Polonia - Mauludiah, Shabrina; Sagala, Indah Cahya (Mahesa Research Center, 2025)
Taxes are the main source of state revenue, contributing over 70% to the national budget, making individual taxpayer (WPOP) compliance crucial for national development. This study analyzes the influence of modern tax administration systems, service quality, and tax sanctions on WPOP compliance at KPP Madya Medan. Using a quantitative approach with data from 2018–2022, the results show that all three variables positively affect tax compliance. Digital systems simplify reporting, good service enhances comfort, and strict sanctions promote discipline. The findings highlight the need for an integrated approach combining technology, service improvement, and fair law enforcement. Practical implications include the importance of digital education, better service delivery, and consistent sanction implementation to sustainably improve tax compliance.